2017
DOI: 10.1007/s40430-017-0819-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of surface roughness using cutting parameters, force, sound, and vibration in turning of Inconel 718

Abstract: discontinuity or gradual corrosion. Therefore, surface roughness investigation is essential for number of applications concerned with the control of friction, fatigue, and wear of parts [1]. Nowadays, machines work at higher speeds and loads which need higher dimensional and geometrical accuracies along with surface quality of the finished parts like bearings, seals, shafts, machine ways, gears, etc. The ability of a manufacturing process to produce desired surface finish depends on machine tool, cutting proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…As reported by Deshpande et al [2], attaining good finish is very tough for Inconel 718. Hence, authors have reported very extensive statistical study for estimating regression-based R a models.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…As reported by Deshpande et al [2], attaining good finish is very tough for Inconel 718. Hence, authors have reported very extensive statistical study for estimating regression-based R a models.…”
Section: Introductionmentioning
confidence: 52%
“…ANN is an effective tool used for estimation of response factors by considering its easiness, speed and learning ability [18]. Therefore, to confirm the results obtained by Deshpande et al [2], it was decided to use ANN to the experimental data.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations